Plato’s Political Leadership and The Question of Relevance in Africa’s Politics - Adefarasin, Victor (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2022)
This paper argues the thesis that Plato’s political philosophy is highly relevant to Africa’s politics. Africa’s politics is characterized by a lot of crises such as corruption and other social maladies. Some of the so called leaders are not well trained; contrary to Plato’s political blue print. Some of African leaders are far from physical and psychological perfection. Acquisition of private property is also a serious issue in Africa’s politics. It is against this background that the paper addresses all these contending issues militating against Africa’s political system which will of course, affect her quest for development. The paper therefore discusses Plato’s political philosophy and its relevance to Africa’s politics. The paper concludes that Plato’s political philosophy is of vital importance to Africa’s politics.